DEVELOPMENT PROGRAM FOR CALCULATION OF MATERIAL DIFFUSION COEFFICIENT IN SURFACE ENGINEERING - Jan Setiawan (Pusbindiklat - LIPI, 2012)
A program to calculate the diffusion coefficient and predicting the depth, time and temperature of diffusionhas been developed. It is shown that the calculation result is in good agreement with the known conventionalone. The program has been developed using Visual Basic based on the Fick’s II law and the diffusion coefficientequation as an exponential function of temperature. It is argued that the program could improve the accuracy ofthe calculation of diffusion coefficient, depth, time and temperature which are important to improve the diffusionprocess efficiency.